2007
DOI: 10.1016/j.chemgeo.2007.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth elements complexation with humic acid

Abstract: The binding of rare earth elements (REE) to humic acid (HA) was studied by combining ultrafiltration and Inductively Coupled Plasma Mass Spectrometry techniques. REE­HA complexation experiments were performed at various pH conditions (ranging from 2 to 10.5) using a standard batch equilibration method. Results show that the amount of REE bound to HA strongly increases with increasing pH. Moreover, a Middle-REE (MREE) downward concavity is evidenced by REE distribution patterns at acidic pH. Modelling of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
229
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(248 citation statements)
references
References 59 publications
15
229
3
1
Order By: Relevance
“…The purification process performed after the extraction causes a significant loss of cations, thereby decreasing the elemental concentration. Very few of the metallic elements detected can be incorporated into the CHA structure because of the capacity of the CHA to bind many heavy metallic ions through complexation [31,32]. Other elements such as Si can originate from impurities.…”
Section: Resultsmentioning
confidence: 99%
“…The purification process performed after the extraction causes a significant loss of cations, thereby decreasing the elemental concentration. Very few of the metallic elements detected can be incorporated into the CHA structure because of the capacity of the CHA to bind many heavy metallic ions through complexation [31,32]. Other elements such as Si can originate from impurities.…”
Section: Resultsmentioning
confidence: 99%
“…This result corroborates Palumbo et al (2005) studies on the affinity of REEs to oxides, where it was reported that Fe, Al and Mn (hydr) oxides can co-precipitate, adsorb and incorporate various REEs in their structure, in amounts varying with type (Wang et al, 2001), depth (Yan et al, 1999) and soil pH (Hu et al, 2006), and sometimes without correlation with Fe and Mn contents (Yan et al, 1999). Organic matter can also retain significant amounts of REEs, because it can complex, adsorb or chelate positively charged REEs in amounts varying with the type, composition and content of OM, soil pH and redox conditions (Pourret et al, 2007). The adsorption of REEs increases with increasing soil pH and CEC values because the surface of soil particles charged with OH -increases as the soil pH increases, thus increasing CEC values.…”
Section: Correlation Studymentioning
confidence: 99%
“…The linear free energy relationship (LFER) or the correlation between the first hydrolysis constant for aqueous species and the corresponding surface complexation constant was used to estimate the sorption stability constant as has been previously done in numerous studies [16,28,36,37]. The LFER can be used to extend results from a limited dataset to other metals.…”
Section: Extrapolation Of the Linear Free Energy Relationshipmentioning
confidence: 99%